(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This report proposes to describe and discuss the process of creating the dramaturgy and staging of the play Soledad from the perspective of decolonial thinking, registering elements that contribute to proposing Latin American creative processes in a southern gaze. The play starts from the story of activist and poet Soledad Barrett Viedma, victim of the Brazilian military dictatorship in 1973, and stories of insurgent women. By analyzing the process of creation of Soledad, the study identified the paths of imagery and dramaturgical construction, highlighting the allegories of the play.